2017
DOI: 10.3892/ol.2017.7122
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated expression of TSHR is associated with distant metastasis in thyroid cancer

Abstract: Abstract. In differentiated thyroid cancer (DTC), the association between thyroid-stimulating hormone receptor (TSHR) and metastasis, and the underlying molecular mechanisms remain unclear. The role of TSHR in the epithelial-mesenchymal transition (EMT) has not yet been reported, to the best of our knowledge. In the present study, the role of TSHR in the distant metastasis of DTC was investigated. TSHR was significantly downregulated in well-differentiated thyroid cancer cells and tissues, and a lack of TSHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Tg and Tshr expression levels were undetectable in all cell lines. Similar to thyroid transcription factors, loss of Tg and Tshr expression has been associated with disease progression [ 27 , 28 ]. Shweppe et al and Henderson et al similarly reported varying expression of thyroid-specific genes in their patient-derived thyroid cancer cell lines [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tg and Tshr expression levels were undetectable in all cell lines. Similar to thyroid transcription factors, loss of Tg and Tshr expression has been associated with disease progression [ 27 , 28 ]. Shweppe et al and Henderson et al similarly reported varying expression of thyroid-specific genes in their patient-derived thyroid cancer cell lines [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…EZH2‐induced silencing of Vash1 by promoter methylation has been implicated in the progression and metastasis of several cancers [Lu et al ]. Liu et al [] also reported that a lack of expression of Tshr was associated with distant metastasis and a poor survival rate. Mmp23 was downregulated in prostate cancer [Riddick et al ], while Lpar33 was downregulated in pancreatic malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that a lack of TSHR contributes to the formation of distant metastasis in patients with differentiated thyroid cancers (DTC), which results in a poor survival rate. The expression of TSHR down-regulates cancer cell invasion by inhibiting the epithelial-mesenchymal transition (EMT) of differentiated thyroid cancer cells [38].…”
Section: Prace Poglądowementioning
confidence: 99%
“…W badaniu wykazano, że brak TSHR sprzyja tworzeniu przerzutów u pacjentów ze zróżnicowanymi rakami tarczycy (DTC, differentiated thyroid cancer), co skutkuje gorszym rokowaniem. Natomiast ekspresja TSHR obniża inwazję komórek nowotworowych poprzez hamowanie przejścia nabłonkowo-mezenchymalnego (EMT, epithelial-mesenchymal transition) komórek DTC [38].…”
Section: Prace Poglądoweunclassified